Pemberdayaan dan Dukungan untuk Ibu Rumah Tangga melalui Kewirausahaan - Sulistya Rini Pratiwi; Meylin Rahmawati; yohanna Thresia Nainggolan; Ferica Christinawati Putri; Kartini; Rahmi Nur Islami; Rizky Agusriyanti Irna; Tanti Try Lestari; Rika Wahyuni Arsianti; Mulyadi; Djuanda Hatta (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The involvement of women in the productive business sector will lead to social change. The entry of women into the labor market or productive work affects household economic activities, resulting in changes in the family's economic structure. This became the rationale for this PKM activity to be carried out. The partners for this activity were a group of housewives in RT 65, Karang Anyar sub-district and Beringin Area, which became the basis for the premise that it was very necessary for this group of housewives to be provided with entrepreneurial skills and product-making skills that could be developed to improve the family economy. The problems of this group of housewives include: there is no guidance in increasing the empowerment of housewives, community activities have not been directed at increasing the knowledge and skills of housewives in terms of their contribution to improving family welfare, community activities that have narrowed into productive economic activities have not been implemented, Entrepreneurial activities for housewives are very limited and have not been developed and there is no stimulant assistance in the form of training and tools that are in accordance with their interests and skills as an incentive to apply their potential. The solution taken is training in product manufacturing skills and an understanding of entrepreneurship.